The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/bcr-2015-210850
|View full text |Cite
|
Sign up to set email alerts
|

Aborted sudden cardiac death associated with an anomalous right coronary artery

Abstract: SUMMARYCoronary artery anomalies arising from the opposite sinus of Valsalva and having an interarterial course between the aorta (AO) and pulmonary artery (PA) are the second most common cause of sudden cardiac death among young athletes, after hypertrophic cardiomyopathy. The right coronary artery (RCA) originating from the AO above the left sinus of Valsalva (LSV) is an extremely rare anomaly. We report the first case of a RCA arising from the AO above the LSV that subsequently runs between the AO and the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Similarly, one autopsy study showed that 38-66% of ACAOS cases were asymptomatic before death and 75-83% died during exercise [ 6 ]. Previous case reports suggested that SCEs in young runners can be attributed to R-ACAOS-IM [ 7 , 8 ]. Typical acute waveforms of ischemic events in R-ACAOS-IM patients are indicated as ST-segment elevations of up to 0.2 mV in leads II, III, and aVF, and subsequent waveforms as normalized ST-segment elevations and negative T-waves in leads II, III, and aVF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, one autopsy study showed that 38-66% of ACAOS cases were asymptomatic before death and 75-83% died during exercise [ 6 ]. Previous case reports suggested that SCEs in young runners can be attributed to R-ACAOS-IM [ 7 , 8 ]. Typical acute waveforms of ischemic events in R-ACAOS-IM patients are indicated as ST-segment elevations of up to 0.2 mV in leads II, III, and aVF, and subsequent waveforms as normalized ST-segment elevations and negative T-waves in leads II, III, and aVF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery anomalies arising from the opposite sinus of Valsalva are the second most common cause of sudden cardiac death among young athletes after hypertrophic cardiomyopathy [6].…”
Section: Discussionmentioning
confidence: 99%
“…En la actualidad, la ACTC es una técnica de diagnóstico eficaz e ideal para la evaluación de pacientes jóvenes con sintomatología cardiaca y alta sospecha de una AC 10,30 . En este estudio, la paciente 5 que sufrió un colapso cardiovascular por una fibrilación ventricular mientras participaba en una maratón, había comenzado a presentar disnea de esfuerzo dos meses antes del evento.…”
Section: Discussionunclassified
“…Su evaluación cardiológica incluyó un ecocardiograma bidimensional y un test de esfuerzo que fueron normales. Sin embargo, el diagnóstico pudo haberse hecho si una ACTC hubiese sido realizada 29,30 . La ACTC es un complemento indispensable para aquellos pacientes cuyo diagnóstico inicial se ha hecho mediante ACI, en los que no fue posible determinar el trayecto del vaso anómalo.…”
Section: Discussionunclassified